The Impact of Thiopurine Metabolite Monitoring on the Durability of Thiopurine Monotherapy in Pediatric IBD. Issue 1 (16th June 2018) - Spencer, Elizabeth; Norris, Evan; Williams, Chadwick; Dubinsky, Marla C
Abstract: Background: Thiopurine metabolite monitoring to proactively dose optimize to achieve therapeutic levels has not been used consistently, and it is unclear if this would lead to better outcomes. We aimed to compare 6-month outcomes between standard and optimized dosing strategies and define long-term predictors of thiopurine durability. Methods: Two hundred sixteen pediatric IBD patients with at least 2 6-thioguanine nucleotide (6-TGN) levels were grouped for analysis by start dose: >2.5 mg/kg/day AZA (group 1) or <2.5 mg/kg/day (group 2) and further subgrouped depending on whether dosing was optimized to achieve 6-TGN >235 pmol/8 × 10 8 RBC. The metabolites, 6TGN and 6MMP, were univariate and multivariate analyses tested associations among metabolite levels, laboratory data, and the primary outcome of 6-month steroid-free clinical remission (SFR) (HBI ≤4 for CD; partial Mayo Score [pMS] ≤2 for UC). Thiopurine durability was measured using Kaplan Maier survival analysis. Results: 6-MP, azathioprine, pediatrics, therapeutic drug monitoring, pediatrics were measured a median 59 (43–76) days after initiation of thiopurine. Both dosing strategies led to similar initial 6-TGN levels (group 1 = median 209 [IQR: 155–272] with 25% of patients >235; group 2 = 196 [139–274] with 29% >235). Steroid-free clinical remission was achieved in 74% of the 180 still on thiopurines at 6 months. Start dose was not associated with 6-month SFR—73% in group 1 and 77% in group 2 within those on thiopurines at 6 months ( P = 0.61). Fixed- and optimized-dosing subgroups had similar 6-month 6-TGN levels, SFR rate, and percentage 6-TGN > 235. Only 6-TGN level >235 at 6 months predicted thiopurine durability (3 years [1.7–7.7] vs 2.5 years [0.83–5]; log-rank P < 0.001), and this did not retain significant in a multivariate model. Initial dosing strategy, first 6-TGN level, 6-month SFR, 6MMP:6TGN ratio, and delta-MCV did not predict durability. The rate of adverse events was 22%. Conclusions: Steroid-free clinical remission and 6-TGN levels at 6 months were no different between a standardized, fixed dosing strategy and a metabolite-driven, optimized dosing strategy.